Late Glacial summer paleohydrology across Central Europe. ... - Prochnow, Maximilian; Hepp, Johannes; Strobel, Paul; Zech, Roland; Acharya, Sudip; Szidat, Sönke; Rius, Damien; Millet, Laurent; Glaser, Bruno; Zech, Michael (University of Bern, 2024)
It is generally accepted that a weakening of the North Atlantic thermohaline circulation caused the Younger Dryas cooling. Although the role of seasonality was emphasized previously, this aspect is rarely considered yet, and it remains elusive how this impacted hydroclimate during winters and summers across Central Europe. Here, we coupled biomarker-based δ18O and δ2H from Bergsee in southern Germany to reconstruct deuterium excess as a proxy for evaporation history from the Bølling-Allerød to the Preboreal. We compared this dataset with other biomarker isotope records in Central Europe. They are all lacking a strong isotopic depletion during the Younger Dryas, which is best explained by the summer sensitivity of the biomarker proxies: As Younger Dryas summers were relatively warm, there is an absence of the strong winter cooling signals recorded in annual water isotope records like Greenland or Lake Steißlingen. Lake evaporation at Bergsee together with other paleohydrological reconstructions draw a ...